Experimental Study on the Use of Rice Husk Ash as Partial Cement Replacement in Aerated Concrete - Saand, A.; Ali, T.; Keerio, M. A.; Bangwar, D. K. (Engineering, Technology & Applied Science Research, 2019)
This paper adopts an experimental approach on the use of rice husk ash as a partial replacement of cement in the production of concrete and the consequent effects on density, compressive strength and split tensile strength of the formulated product. Rice husk ash is used as replacement of cement in different dosages of 0%, 2.5%,5%, 7.5%, 10%, 12.5%, and 15%. Results showed that 10% replacement of cement with rice husk ash is optimum. At 10% replacement of cement with RHA, the density is increased by 5.02%, the compressive strength by 22.22% and the split tensile strength by 20.45% in comparison with control aerated concrete.